Emerging Needs of People Living With HIV Receiving Community‐Based Nursing in an Australian Setting. (July 2017) - Crock, Elizabeth A.; Miller, Charne; McKenzie, Rosemary; Burk, Nalla; Frecker, Judith; Hall, John E.; Ramirez, Oscar Morata
Abstract : N/A: While the lifespan of people living with HIV (PLWH) in Australia has increased, a minority still experience poor health outcomes and have complex needs. Few studies address this group's emerging needs. Our study, a component of a larger evaluation, aimed to identify current and projected needs of PLWH receiving HIV community nursing. We undertook a cross‐sectional survey to identify clients' support needs and explore their future concerns. There were 120 of 140 PLWH who met our eligibility criteria to participate in the survey; 86 responded. Respondents overrepresented minority, disadvantaged groups. Mental health support was the most common care reported (86.8%). Respondents' self‐identified needs included access to health care, dealing with pain, anticipated grief due to friends dying, and maintaining independence. Time since HIV diagnosis and sexual orientation were primary variables for which differences were observed. Our study highlights the importance of developing and sustaining HIV specialist community nursing services for aging PLWH.